Meninos de Veiga Valle: um olhar aprofundado sobre as obras do artista - Ana Carolina de Souza Cruz (2021)
The study of Brazilian colonial sculptures has been deepening over the years, especially in the states of Minas Gerais, Rio de Janeiro, Bahia and São Paulo. The research about devotional images that are not found on the coast has also gradually been done by the countryside. Thus, the aim of this work was to investigate the gilded and polychromy wood sculptures attributed to the artist José Joaquim da Veiga Valle (1806-1874), located in the Museum of Sacred Art of Boa Morte, in the city of Goiás/GO. The literature review about the artist showed recurrence in the assertion that Veiga Valle was knowledgeable in the techniques of sculpture, painting and gilding, based mainly on oral tradition, with interviews conducted by Rescala with his living descendants in 1940. This assertion made us raise some hypotheses, because these trades were executed by different professionals in previous centuries. Authors such as Salgueiro (1983) and Passos (1997) reinforced the claims of oral tradition and emphasized the artist's sculptural and pictorial technical quality. The qualitative comparative analysis was realized in 17 images of the Menino Deus (Infant God) and the Menino Jesus (Infant Jesus), as a study case, since they represent the same iconography and we consider his more expressive works. The images were studied especially in regard to their form and polychromy. In addition, photographic documentation and examinations with magnifying glasses, special lights, X-rays, and the collection of samples for laboratory analysis were essential to complement the research. As results, we verified similarities between some sculptures and the confection in single and massive blocks (the majority); variety in the type of glass eyes (when it is existent); confirmation of the presence of white lead pigment in the polychromy, and the use of angico-vermelho (red angico) as the wood used by the sculptor in the two analyzed images. The results ratified that the materials and techniques used are in accordance with the sculptures made in the 19th century, the period in which Veiga Valle worked. This research allowed us to raise some hypotheses about the production of group works (carving and polychromy) and to indicate the existence of a Veiga Valle workshop, in which the artist worked with officers and apprentices, besides his son. The investigation provided a deeper knowledge about the sculptures attributed to Veiga Valle, a symbol of the devotional imagery of 19th century Goiás. The interdisciplinary work of several fields of knowledge was essential for this research.